Solutions to Overcome Burnout Symptoms in Nurses in the Covid-19 Isolation Room - Kurniawan, Sylvia Jessy; Gede Utara Hartawan, I Gusti Agung; Rusca Putra, Kuswantoro (Jurnal Kedokteran Brawijaya, 2024)
The Covid-19 pandemic has left healthcare workers working in uncertain and stressful situations to care for all patients with disabilities. The second wave of the Covid-19 pandemic that swept across the world caused many nurses in health facilities to experience fatigue in carrying out their duties. This study aims to determine the cause of burnout symptoms in isolation room nurses in the Covid-19 pandemic. The study was conducted at X Hospital in September-October 2021. The design of this study was descriptive analysis. Observations were made on the service system, data, and environment of the Covid-19 isolation room at X Hospital. Interviews and discussions were conducted with the head nurse, the head of the occupational safety and health committee, and the head of nursing medical services related to nurse burnout in the isolation room. 67.74% experienced emotional exhaustion in the medium and high categories in isolation room nurses in the second wave of the Covid-19 pandemic caused by a lack of staffing. The solution to detect and overcome burnout is to conduct mental health checks and regular medical check-up programs for further treatment by considering the comfort factor and high functional value.